2014
DOI: 10.3174/ajnr.a3903
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spectrum of In Utero Structural Brain Abnormalities in Fetuses with Complex Congenital Heart Disease

Abstract: BACKGROUND AND PURPOSE:Brain injury is a major complication in neonates with complex congenital heart disease. Preliminary evidence suggests that fetuses with congenital heart disease are at greater risk for brain abnormalities. However, the nature and frequency of these brain abnormalities detected by conventional fetal MR imaging has not been examined prospectively. Our primary objective was to determine the prevalence and spectrum of brain abnormalities detected on conventional clinical MR imaging in fetuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 26 publications
6
74
3
Order By: Relevance
“…Our group has previously shown that neurodevelopmental impairments and brain injury in CHD has its origins in the fetal period, where impaired brain growth and delayed maturation can be detected by advanced MRI (3639). Alterations in the fetal circulation caused by CHD have been associated with changes in cerebral blood flow and oxygen delivery to the brain, and in turn may contribute to disrupted fetal brain development and long term neurodevelopmental impairments (38).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that neurodevelopmental impairments and brain injury in CHD has its origins in the fetal period, where impaired brain growth and delayed maturation can be detected by advanced MRI (3639). Alterations in the fetal circulation caused by CHD have been associated with changes in cerebral blood flow and oxygen delivery to the brain, and in turn may contribute to disrupted fetal brain development and long term neurodevelopmental impairments (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown high correlations between head circumference at birth and both brain weight and brain volume, and thus head circumference at birth is considered to be a useful proxy for cerebral size. [44][45][46] A previous MRI study reported an increased prevalence of ventriculomegaly and increased extraaxial spaces in fetuses with CHD, 47 and thus an extrapolation from a difference in head circumference at birth to a difference in cerebral size may underestimate the actual difference. Standardization by gestational age at birth may in some cases induce spurious associations.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Using MRI and cranial ultrasound as early as 18 wk gestation, CHD fetuses-including those with HLHS-were consistently shown to have smaller head circumference (30), increased prevalence of brain abnormalities (9), lower total brain volume (31), and white matter (WM) abnormalities (9,30). Growth rates in head circumference; cerebral total, GM, and WM volumes; and brain metabolic biomarkers are slower for CHD fetuses relative to controls.…”
Section: Articles Watson Et Almentioning
confidence: 99%
“…Differences in brain structure of CHD patients have been documented in utero (9). Even prior to initial surgery, which often occurs in the neonatal period, signs of brain injury and abnormal cerebral hemodynamics are apparent both in autopsy and MRI studies (10,11).…”
mentioning
confidence: 99%